Biography in numbers: a historiometric case study - Modrzejewska-Świgulska, Monika; Agnieszka Gralak, Łukasz Zieliński (Biograficzne badania nad twórczością. Teoria i empiria, 2016)
In the historiometric case study described in the chapter, a nomothetic and idiographic approach was described, thus creating a unique possibilities of research into outstanding creativity. Previously, pedagogy and psychology noted few publications that would apply this not so common technique. Thus, an attempt was made to describe the main historiometric assumptions, a case study which would indicate its differences to other research solutions, what are the opportunities it presents, challenges and threats.Praca naukowa finansowana w ramach programu Ministra Nauki i Szkolnictwa Wyższego pod nazwą „Iuventus Plus” w latach 2015–2016 nr projektu 0252/IP3/2015/73.